INTEGRITAS GURU DALAM PERSPEKTIF HADIS: URGENSI KEJUJURAN DAN KETELADANAN SEBAGAI PILAR PENDIDIKAN: Integritas Guru; Hadis Tarbawi; Keteladanan; Kejujuran - Abdul Fatah, Nurlaila Balqis; Adawiyah, Riri Robiatul; Ar Rasyid, Fathan Ahmad; Muhammad Rendi Ramdhani (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
The urgency of teacher integrity is a serious issue in the world of education, especially in shaping the character of students. Teachers do not only act as educators, but also as moral role models for their students. In the perspective of the hadith tarbawi, the values ​​of honesty and exemplary behavior are the main pillars of forming a teacher's integrity. This study aims to examine in more depth how these values ​​can shape the integrity of educators and influence students' behavior and attitudes. The method used is a literature study with a descriptive qualitative approach. The results of the study show that teachers who are honest, fair, and able to be real examples in everyday behavior have a major influence in shaping the character of students. The honesty of teachers in assessing, as well as their consistency in words and actions, are important measures in building student trust. This study is expected to contribute to strengthening the professionalism of teachers who are not only intellectually intelligent, but also morally and spiritually strong. This description has proven to be a prime example for the students themselves. The impact that we obtained was that in addition to being a source of knowledge, this research provided a number of exploratory knowledge of some things that need to be applied and not done in an institution that is oriented towards becoming a culture so that it is good and is believed to be able to produce a society and nation that develops and advances on the path of Allah SWT.